Peningkatan keterampilan menulis teks narasi melalui model pembelajaran circuit learning pada peserta didik kelas v sekolah dasar - Fulusia Nurmawati; Rukayah Rukayah; Tri Budiharto (Didaktika Dwija Indria, 2020)
The purpose of this study was to improve the narrative text writing skills through the Circuit Learning model in the fifth grade students of SD Negeri Tegalsari No. 60 Academic Year 2018/2019. The subjects of this study were classroom teachers and fifth grade students at SD Negeri Tegalsari No. 60 Academic Year 2018/2019 totaling 30 students. This research uses interview, observation, test and documentation techniques. Analysis of the data of this research is data collection, data reduction, data presentation and drawing conclusions. The data validity technique uses content validity, source triangulation and technique triangulation. The results of this study indicate that the use of the Circuit Learning learning model can improve narrative text writing skills in each cycle. Data from the results of the pre-action is that there is no complete KKM, in the first cycle the classical completeness results obtained in that class amounted to 41.18%, then in the second cycle of 82.35%. Based on the description above, it can be concluded that the application of the Circuit Learning learning model can improve narrative text writing skills in fifth grade students of SD Negeri Tegalsari No. 60 of 2018/2019.